Price vs Quantity in a Dynamic Duopoly Game with Capacity Accumulation - Luca Lambertini; Roberto Cellini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2002)
We present a differential duopoly game with capacity accumulation, wherethe closed-loop memoryless Nash equilibrium collapses into the open-loop Nash equilibrium. Sy mmetric Bertrand and Cournot equilibria are observationally equivalent. This result encompasses the conclusions of the well known model Kreps and Scheinkman (1983) concerning the equivalence between the Bertrand and Cournot settings in a static two-stage game. However, in the dynamic framevork, the equilibrium outcome is different, when one firm plays à la Bertrand and the other à la Cournot. This has relevant bearings upon firms` endogenous choice of the market variable, as well as the social desirability of prices vs quantities. For some admissible parameter ranges, the conflict between private and social incentives concerning the choice between prices and quantity disappears.
Keywords: 330